Motivation, Phrase, and Illusion Tutor on Instagram Accounts: Pragmatic Analysis Study - Sufyana Sufyana; Muhafizah el-Feyza; M. Riyan Hidayat; Kristina Imron; Bakhrum Amir (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padngsidimpuan, 2023)
Lately, social media platforms, especially Instagram, are busy making memes as icons in every upload of message delivery. The creative design presented can attract the attention of netizens so that they can make the meme something that is favored by social media audiences. This article aims to describe the speech forms presented and uploaded by the Instagram account @motivasi.penghafal.al-quran and to describe how the function of the speech it conveys in the form of sentences designed into memes. The method used is descriptive-qualitative. The data collected was obtained from meme uploads about the motivation of memorizing the Qur'an on the Instagram account @motivasi.penghafal.al-quran. The utterances contained in each upload are analyzed using pragmatic theory. The results of this study indicate that the utterances uploaded to the Instagram account @motivasi.penghafal.al-quran are grouped based on their form and function, including; declaration, representation, expressive, directive, and commissive functions.